The focalizations of the sick person in the story ‘Report about Diego Ames’, by Jorge Valenzuela Garcés - Tarrillo Bazán, María Laura (2021)
This article studies focalizations, also known as ‘points of view’, that are held about Diego Ames, the sick psychopath character in the tale Report on Diego Ames, made by peruvian writer Jorge Valenzuela Garcés. The author chooses a narrator who tells the story through two types of focus: the focus of the psychologist and the focus of the environment of the sick person. Through these views we see what Diego Ames was like, what psychological characteristics he had, how he related to others, how he committed the murder of his father, a leading peruvian politician, how this crime was seen and how in fiction his case focused on the mental health of an entire country due to the social and political context in which the events unfold. Likewise, the story allows us to review the treatment of the disease in literature, throughout history, and analyze the political and social context of Peru in the year in which it was written, in 2007.